The impact of immobilisation and inflammation on the regulation of muscle mass and insulin resistance: different routes to similar end points - Crossland, Hannah; Skirrow, Sarah; Puthucheary, Zudin A.; Constantin-Teodosiu, Dumitru; Greenhaff, Paul L. (Wiley, 2018)
Loss of muscle mass and insulin sensitivity are common phenotypic traits of immobilisation and increased inflammatory burden. The suppression of muscle protein synthesis is the primary driver of muscle mass loss in human immobilisation, and includes blunting of post‐prandial increases in muscle protein synthesis. However, the mechanistic drivers of this suppression are unresolved. Immobilisation also induces limb insulin resistance in humans, which appears to be attributable to the reduction in muscle contraction per se. Again mechanistic insight is missing however, such that we do not know how muscle senses its “inactivity status” or whether the proposed drivers of muscle insulin resistance are simply arising as a consequence of immobilisation. An heightened inflammatory state is associated with major and rapid changes in muscle protein turnover and mass, and dampened insulin‐stimulated glucose disposal and oxidation in both rodents and humans. A limited amount of research has attempted to elucidate molecular regulators of muscle mass loss and insulin resistance during increased inflammatory burden, but rarely concurrently. Nevertheless, there is evidence that Akt (protein kinase B) signalling and FOXO transcription factors form part of a common signalling pathway in this scenario, such that molecular cross‐talk between atrophy and insulin signalling during heightened inflammation is believed to be possible (Fig. 1). To conclude, whilst muscle mass loss and insulin resistance are common end‐points of immobilisation and increased inflammatory burden, a lack of understanding of the mechanisms responsible for these traits exists such that a substantial gap in understanding of the pathophysiology in humans endures.